2009
DOI: 10.1021/ma901359x
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization ofl,l-Lactide: Kinetic and Modeling Study

Abstract: Ring-opening polymerization of L,L-lactide with various amounts of catalyst, 2-ethylhexanoic acid tin(II) salt, and cocatalyst, 1-dodecanol, at 130 °C in bulk is examined. Monomer-to-catalyst and cocatalyst-to-catalyst molar ratios were changed from 500 to 4000 and from 1 to 600, respectively. In agreement with previous literature, the catalyst concentration is affecting the reaction rate, whereas OHbearing species (such as cocatalyst and impurities) are controlling both reaction rate and polymer molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(147 citation statements)
references
References 43 publications
11
134
2
Order By: Relevance
“…Note that at high monomer conversions and high polymerization temperatures (i.e., higher than 130 °C), scission and trans‐esterification reactions become important, resulting in a decrease of Mtrue‾normalw and an increase of polydispersity index. On the other hand, at low polymerization temperatures, their contribution to the molecular weight developments is not significant . The experimentally measured values of the polydispersity index (i.e., Mtrue‾normalw/Mtrue‾normaln) varied from 1.0 to 2.6.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Note that at high monomer conversions and high polymerization temperatures (i.e., higher than 130 °C), scission and trans‐esterification reactions become important, resulting in a decrease of Mtrue‾normalw and an increase of polydispersity index. On the other hand, at low polymerization temperatures, their contribution to the molecular weight developments is not significant . The experimentally measured values of the polydispersity index (i.e., Mtrue‾normalw/Mtrue‾normaln) varied from 1.0 to 2.6.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, it is of paramount importance to precisely know their concentration since they largely affect the polymerization rate and molecular weight of PLLA . In order to ensure accurate control of the concentration of all possible sources of hydroxyl bearing species, the polymerization is usually carried out in the presence of a known concentration of an alcohol (i.e., a co‐initiator), which is actually the dominant source of hydroxyl groups . In the present study, the only source of hydroxyl groups was the residual water moisture present in the polymerization recipe.…”
Section: Resultsmentioning
confidence: 98%
“…The GPC and MALDI-TOF data are in a good agreement, and we observed that the most abundant species are the macromonomers with an even number of lactoyl units (as expected, LT was a dimer). 27 26 The same procedure that was used to produce and verify the effective HPMA-LA 8 was applied for the lower MW macromonomers, specifically, HPMA-LA 4 and HPMA-LA 6 .…”
Section: Macromonomer Synthesismentioning
confidence: 99%
“…The experimental evidence of the exchange reactions is broadening of molar mass distribution which can be detected by Size Exclusion Chromatography (SEC) at the late polymerization stages. [7][8][9][10][11] Penczek, et. al. conducted kinetic studies and numerical modelling of the segmental exchange reactions, leading to the introduction of a selectivity/reactivity parameter for this system.…”
mentioning
confidence: 99%